Diagnosing Career Plateau for Employees of the General Directorate of Education Karkh First: a Case Study (مجلة المنصور, 2023)
The aim of the research is to diagnose the career plateau in the General Directorate of Cherry 1. To that end, the functional plateau variant was measured in four sub-dimensions (structural plateau, job content plateau, occupational plateau, The personal collection of the research sample (the general manager, his assistants, department heads and directors of divisions and units at the directorate and division levels) was intentionally represented by a community represented by the General Directorate of Baghdad Education, the first Karkh, and all its departments in the city of Baghdad. The researcher distributed (282) questionnaires to the research community. The data were collected from (275) respondents using the resolution that included 28 paragraphs, and included them with interviews and field observations as helpful tools in promoting them. The research program (SPSS V.28) was adopted with statistical methods descriptive, and the research came up with a set of results, the most important of which is a clear and moderately career plateau.